A Flatness Based Nonlinear Sensorless Control of Induction Motor Systems - Berrezzek Farid; Bourbia Waffa; Bensaker Bachir (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper deals with  the flatness based approach for sensrless  control of induction motor systems.Two main features of the proposed flatness based control are worth to be mentioned. Firstly, the simplicity of implementation of the flatness approach as a nonlinear feedback linearization control technique. Secondly, when the chosen flat outputs involve non available state variable measurements a nonlinear observer is used to estimate them. The main advantage of the used observer is its ability to exploite the properties of the system nonlinearties. The simulation results are presented to illustrate the effectiness of the proposed approach for sensorless control of the considered induction motor.